RANCANG BANGUN GAME EDUKASI PENANGANAN SAMPAH DALAM RANGKA PEDULI LINGKUNGAN BERBASIS ANDROID DENGAN METODE REASEARCH AND DEVELOPMENT (R&D) - Najibul Khoir , Achmad; Heru Mujianto , Ahmad; Ali , Mahrus (Inovate, 2024)
Waste has become an urgent issue in the modern era. The lack of environmental concern leads to pollution and environmental damage. The high occurrence of natural disasters, especially hydro-meteorological ones, is caused by human indifference. The unmanaged growth of waste contributes to complex damage and pollution. The low public awareness about waste results in a change in lifestyle that relies on single-use plastics. Insufficient education and curriculum hinder students' understanding of environmental management. The lack of environmental education and awareness poses a barrier to shaping children's character and environmental consciousness. There is a need for increased integration in the curriculum and learning media to strengthen students' understanding of the importance of environmental conservation from an early age. Therefore, this research aims to develop an innovative medium in the form of an interactive game-based application for environmental education and waste management, using the R&D method for game development and incorporating the Fuzzy Sugeno method for implementing the reward system. Key word : Waste, Educational Game, R&D, Fuzzy Sugeno